Synthesis, structure, and photoluminescent property of a Zn(II) coordination polymer with 3-fold parallel interpenetrated network. Issue 8 (3rd August 2017) - Li, Fu-An; Yang, Wei-Chun; Li, Qing-Bin
ABSTRACT: A novel coordination polymer, [Zn(L)(1, 4-bbi)0.5 ] n (1 ), where H2 L = 5-(4-hydroxypyridinium-1-ylmethyl)isophthalic acid, 1, 4-bbi = 1, 1′-(1, 4-butanediyl)bis(imidazole), has been hydrothermally synthesized and structurally characterized by X-ray diffraction analysis and further characterized by infrared spectra, elemental analysis, and thermogravimetric analysis. Compound1 has a two-dimensional (2D) double-layered structure and exhibits the 3-fold parallel interpenetrated 2D → 3D network motifs, and Zn(II) center has distorted trigonal bipyramidal environment. Meanwhile, the luminescent property of the compound has also been investigated in detail.